A novel method for the purification of inositol phosphates from biological samples reveals that no phytate is present in human plasma or urine. Issue 3 (March 2015) - Wilson, Miranda S. C.; Bulley, Simon J.; Pisani, Francesca; Irvine, Robin F.; Saiardi, Adolfo
Abstract : Inositol phosphates are a large and diverse family of signalling molecules. While genetic studies have discovered important functions for them, the biochemistry behind these roles is often not fully characterized. A key obstacle in inositol phosphate research in mammalian cells has been the lack of straightforward techniques for their purification and analysis. Here we describe the ability of titanium dioxide (TiO2 ) beads to bind inositol phosphates. This discovery allowed the development of a new purification protocol that, coupled with gel analysis, permitted easy identification and quantification of InsP6 (phytate), its pyrophosphate derivatives InsP7 and InsP8, and the nucleotides ATP and GTP from cell or tissue extracts. Using this approach, InsP6, InsP7 and InsP8 were visualized in Dictyostelium extracts and a variety of mammalian cell lines and tissues, and the effects of metabolic perturbation on these were explored. TiO2 bead purification also enabled us to quantify InsP6 in human plasma and urine, which led to two distinct but related observations. Firstly, there is an active InsP6 phosphatase in human plasma, and secondly, InsP6 is undetectable in either fluid. These observations seriously question reports that InsP6 is present in human biofluids and the advisability of using InsP6 as a dietary supplement.